Antimicrobial Activity of Endemic Herbs from Tangkahan Conservation Forest North Sumatera to Bacteria and Yeast - KIKI NURTJAHJA; TATA BINTARA KELANA; DWI SURYANTO; NUNUK PRIYANI; GINTA RIO; DEDI PRIMA PUTRA; DAYAR ARBAIN (Bogor Agricultural University, Indonesia, 2013)
Tangkahan Conservation Forest in Karo County, North Sumatera has high biodiversity of endemic herbs. Many species of the wild herbs are well known used as traditional medicine not only by local people but also by people out of the area. The methanol extract of the medicinal wild herbs in Tangkahan Conservation Forest, Karo County to relief skin diseases caused by bacteria and fungi never been studied medically. The antimicrobial activity leave extract of the medicinal herbs to pathogenic microorganisms are studied. The leaves extract of kembu-kembu (Callicarpa candicans), rintih bulung (Piper muricatum), cep-cepan (Castanopsis costata), and sereh kayu (Eugenia grandis), has antimicrobial to bacteria (Bacillus sp., Escherichia coli, Serratia marcescens, Staphylococcus aureus) and yeast (Candida albicans). Toxicity assay of these plants by brine shrimp method using Artemia salina indicates that cep-cepan dan sereh kayu have lethal concentration higher than kembu-kembu and rintih bulung.